DAYA TERIMA DAN KANDUNGAN GIZI SELAI DARI KULIT SEMANGKA (Citrullus lanatus) DAN LABU KUNING (Cucurbita moschata) - Nuansa Nungky Nismara; Ernawati Nasution; Jumirah . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
Watermelon rind was an organic waste that can be made as a jam ingredients because it was easy to process and has nutrient content. Jam was a thick textured food product made by fruits mixed with sugar. Pumpkin was added in the making of jam to improve the characteristics of jam and increase the nutrient content in jam. Pumpkin contained high betacarotene which can be a source of provitamin A. This study aimed to determine the acceptability and nutrient content of jam made by watermelon rind and pumpkin. This study was an experimental design using completely randomized design with three treatment combinations of watermelon rind and pumpkin with ratio of 30%:70%, 50%:50% and 70%:30%. The acceptability test was conducted by 30 students of Public Health Faculty of University of Sumatera Utara and the analysis of betacarotene, phosphorus and calcium has done in laboratory of Palm Oil Research Center and Research and Industry Standardization Center Medan. The results showed that based on organoleptic test of color and taste the most preferred jam was jam with ratio of 30%:70%, based on flavor, the most preferred jam was jam with ratio of 70%:30% and based on texture, the most preferred jam was jam with ratio of 50%:50%. Based on the result of Anova One Way test from three treatments of watermelon rind and pumpkin jam showed that there was no significant difference on the acceptability of jam. The highest nutrient content was found in watermelon rind and pumpkin jam with ratio of 30%:70%, that contained betacarotene 71,2 ppm, phosphorus 57,7 mg and calcium 13,6 mg. Watermelon rind and pumpkin jam that contained betacarotene can be made as a topping or filling various types of food, so it can be made as food alternative for children as one of prevention of vitamin A deficiency. Keywords : Jam, Watermelon Rind, Pumpkin, Acceptability, Nutrient Content